Navigator: the paths to the aesthetic experience in art/education - Oliveira, Rafaela Pupin de; Serrano, Eliane Patricia Grandini (Farol, 2021)
This article presents a discussion on the poetic and educational possibilities of the aesthetic experience, a particular form of interaction with artistic objects, both from the point of view of fruition and poetic making. Both can be explored by the art / educator, as a mediator, researcher, and agent in creative processes. These aspects are explored by the navigator's metaphor, who is conceptualized as a subject who is challenged to create his own way to live an experience. Theoretical concepts, the poetic look and their relationships show the importance of “navigating” in challenging moments like the pandemic. The organic and subjective process of experience, the role of the teacher-artist, aesthetic education, and the potential of art in the formation of human beings are identified.
Keywords: aesthetic experience; art/education; mediation; creative process